Bridging Organizational Support and Teacher Self-Efficacy: The Mediating Role of Emotional Intelligence - Muhibbin, Maulana Arif; Danan Satriyo Wibowo; Muhammad Sulton Al Gifari; Nanda Kafila Sari (Journal An-Nafs: Kajian Penelitian Psikologi, 2025)
Teacher self-efficacy reflects educators’ beliefs in their professional competence and plays a critical role in delivering high-quality education. This study investigates the effect of perceived organizational support (POS) on teacher self-efficacy (TSE), with emotional intelligence (EI) examined as a potential mediating variable. Using a quantitative approach, data were collected from 180 secondary school teachers in Jember, Indonesia. The researchers developed adapted instruments to measure POS, EI, and TSE, and employed mediation analysis using PROCESS in SPSS. The results show that perceived organizational support significantly predicts both emotional intelligence (β = 0.1607, p = .0002) and teacher self-efficacy (β = 0.0784, p = .0390). However, emotional intelligence does not significantly predict teacher self-efficacy (β = -0.0457, p = .4796), and the indirect effect of POS on TSE through EI is statistically insignificant. These findings indicate that while POS directly strengthens teacher self-efficacy, emotional intelligence does not mediate this relationship. The novelty of this research lies in its integrative exploration of how perceived organizational support and emotional intelligence interact to influence teacher self-efficacy within the Indonesian context—an area that remains underexplored. Unlike prior studies that examine these constructs in isolation, this study empirically tests a mediation model, offering new insights into the psychological and institutional mechanisms that shape teacher effectiveness. These results underscore the importance of fostering a supportive organizational climate to enhance teacher self-efficacy. The study provides practical implications for educational policymakers to prioritize institutional support systems that directly contribute to teacher development and performance.